Customized protein modification improves human gingival fibroblasts adhesion on SiO2. (December 2021) - Mo, Wenting; Qi, Haoning; Zhang, Fanyu; Shi, Miusi; Zhao, Qin; Shen, Kailun; Ni, Yueqi; Jiang, Shuting; Zhang, Yufeng
Highlights: Fibronectin and vitronectin were the only two adhesive proteins responsible for HGFs adhesion in serum proteins layer on SiO2 and ZrO2 . Vitronectin coating on SiO2 can significantly improve cell adhesion, which was as good as that on vitronectin-coated ZrO2, but fibronectin coating on SiO2 had limited cell adhesion promotion. The affinity difference of fibronectin and vitronectin on SiO2 and ZrO2 caused the cell adhesion difference on them. Abstract: SiO2 -based materials have great potential for dental implant abutment in the future, but the SiO2 itself didn't support cell adhesion well, which could hinder the gingival tissue from forming a favorable seal around the abutment. In this study, SiO2 showed inferior human gingival fibroblasts (HGF) adhesion than ZrO2, the classic abutment material, which was caused by the serum protein affinity difference. By mass spectrometry, fibronectin (FN) and vitronectin (FN) in serum were found to mediate cell adhesion on materials. Single- molecule tracking and molecule dynamics simulation revealed that the affinity between FN and SiO2 was weaker than that of ZrO2, and the cell adhesion on FN-coated SiO2 was not improved as well as that on ZrO2, while the affinity of VN and SiO2 was comparable with that of VN and ZrO2 and the VN-coated SiO2 facilitated the HGF adhesion as effectively as VN-coated ZrO2 . Here, the customized protein modification improved the cell adhesion on SiO2 and promoted the development of the SiO2 -based dental materials. Graphical abstract: Image, graphical abstract